Who made clever hans stupid? - Despret, V.; Chrulew, Matthew (2015)
© 2015 Taylor & Francis. The case of Clever Hans is one of the most notorious episodes in the history of animal psychology. The "Clever Hans effect" has since become the name of a cardinal scientic sin, the experimenter effect by which researchers inadvertently give their subjects the answers to their questions. Yet this discrediting accusation is often overstated, and in need of a careful differentiation. In this section from Vinciane Despret's book Hans she digs through the les to reconsider this famous horse and his psychologists, and thereby, also, provokes us to rethink the legacy of this meaningful scandal in the subsequent history of scientic research on animal intelligence.